Catalytic Hydrolysis of Ammonia Borane by Cobalt Nickel Nanoparticles Supported on Reduced Graphene Oxide for Hydrogen Generation. (14th April 2014) - Yang, Yuwen; Zhang, Fei; Wang, Hualan; Yao, Qilu; Chen, Xiangshu; Lu, Zhang-Hui
Abstract : Well dispersed magnetically recyclable bimetallic CoNi nanoparticles (NPs) supported on the reduced graphene oxide (RGO) were synthesized by one-step in situ coreduction of aqueous solution of cobalt(II) chloride, nickel (II) chloride, and graphite oxide (GO) with ammonia borane (AB) as the reducing agent under ambient condition. The CoNi/RGO NPs exhibits excellent catalytic activity with a total turnover frequency (TOF) value of 19.54 mol H2  mol catalyst −1  min −1 and a low activation energy value of 39.89 kJ mol −1 at room temperature. Additionally, the RGO supported CoNi NPs exhibit much higher catalytic activity than the monometallic and RGO-free CoNi counterparts. Moreover, the as-prepared catalysts exert satisfying durable stability and magnetically recyclability for the hydrolytic dehydrogenation of AB, which make the practical reusing application of the catalysts more convenient. The usage of the low-cost, easy-getting catalyst to realize the production of hydrogen under mild condition gives more confidence for the application of ammonia borane as a hydrogen storage material. Hence, this general method indicates that AB can be used as both a potential hydrogen storage material and an efficient reducing agent, and can be easily extended to facile preparation of other RGO-based metallic systems.